Penerapan AAA Security Dalam Aplikasi BNI Mobile Banking - Dita Ayu Eka Saputri; Ida Ayu Ernawati; Nimas Adjeng Nutfa Rabbaanii; Adibah Dewi Satriani (Institute of Advanced Knowledge and Science, 2023)
Information system security is crucial in the digital era. The application of AAA (Authentication, Authorization, and Accounting) has become a broad approach to protecting data in information systems. This study aims to analyze the application of AAA in improving information system security in BNI Mobile Banking. This research method includes literature and experimental studies which are used as a research approach. The results of the study show that BNI Mobile Banking is sufficient to apply AAA significantly to improve the security of its information system.